ASSOCIATION OF BLOOD TYPE AND MORTALITY OF COVID-19: A HOSPITAL-BASED STUDY IN NATIONAL REFERRAL HOSPITAL, INDONESIA - USMAN , Elly; KATAR, Yusticia (African Journal of Infectious Diseases (AJID), 2023)
Background: The ABO blood type plays an important role in various diseases, such as cancer, cardiovascular, and certain communicable and non-communicable diseases. However, there is currently little definite evidence between COVID-19 with ABO blood types. Aim: The aim of this study was to determine the relationship between ABO blood type and the mortality of patients infected with COVID-19 in a national referral hospital, Indonesia. Methods: This study used a retrospective cohort. The research sample was COVID-19 patients who were in Dr. M. Djamil Hospital Padang. The number of samples in this study was 93 subjects. Data analysis was performed using the Chi-square test. P < 0.05 was significant, and the data were analyzed using the SPSS version 21.0 program. Results: The results of this study found the percentage of mortality of COVID-19 patients was higher for blood group O (46.2%), followed by AB (41.7%), B (26.3%), and A (13.9%). There was a relationship between blood type and mortality in hospitalized COVID-19 patients (p <0.05), where blood type O had the highest risk (OR = 5.31, 95% CI 1.57-17.98) followed by blood type AB (OR = 4.43, 95% CI 1.01-19.58). Conclusion: This study confirmed there was a relationship between blood type and mortality in hospitalized COVID-19 patients, where blood type O had the highest risk followed by blood type AB.